Herman B Wells : The Promise of the American University - Capshew, James H. (Book collections on Project MUSE., 2012)
Energetic, shrewd, and charming, Herman B Wells was the driving force behind the transformation of Indiana University -- which became a model for American public higher education in the 20th century. A person of unusual sensitivity and a skilled and empathetic communicator, his character and vision shaped the structure, ethos, and spirit of the institution in countless ways. Wells articulated a persuasive vision of the place of the university in the modern world. Under his leadership, Indiana University would grow in size and stature, establishing strong connections to the state, the nation, and the world. His dedication to the arts, to academic freedom, and to international education remained hallmarks of his 63-year tenure as President and University Chancellor. Wells lavished particular attention on the flagship campus at Bloomington, expanding its footprint tenfold in size and maintaining its woodland landscape as new buildings and facilities were constructed. Gracefully aging in place, he became a beloved paterfamilias to the IU clan. Wells built an institution, and, in the process, became one himself.